(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that in modern conditions it is important to involve the public in the supervision and control of the activities of public administration entities. After all, public administration in the world context is considered through the prism of globalization, democratization, marketization, decentralization, economic crises, immigration, diversification and growth of needs and demand, detailed analysis of recent events and trends in the field of public administration. One of the leading such trends is public supervision and control in public administration. It is noted that for a deeper look at the essence of public supervision and control in public administration, it is possible to refer to the principles of such activity as its worldview and system-forming foundations. It has been established that among such principles some researchers single out the principle of subsidiarity; principle of participation; the principle of mutual responsibility; the principle of mutual control of the state, business and public institutions; the principle of trust. Among the individual principles of public supervision and control in public administration, the principle of digital humanism is analyzed, which is designed to prevent an exclusively technical approach to the assessment of public opinion, to establish at the level of values the observance of public participation in the control and supervision of the functioning of state institutions, while not limiting this participation and processes of its assessment exclusively in the digital environment; the principle of non-performativeness, the observance of which requires the real participation of the public in the implementation of public supervision and control in public administration, conducting public expertise, public monitoring, public discussions, including on the condition that civil society institutions interact with each other; the principle of wide application of project management technologies in the course of public supervision and control in public administration, which establishes the possibility for the public to participate in improving the forms and methods of public supervision and control through the development and implementation of social projects.